Walker. Season two [videorecording (DVD)] - Allen, Keegan, 1989-; Bell, Coby; Brinson, Violet; Hagan, Molly, 1961- (Paramount, 2022)
Texas Ranger Cordell Walker is more determined than ever to protect his family and find out the truth about his wife's death. Micki goes on a secret ops mission to stop the Del Rio crime syndicate but she realizes it could take a toll on her relationship with Trey. The return of the Davison family ignites an old feud with the Walkers and Liam doesn't trust the new DA. The five-disc set is packed with exclusive special features and all twenty intense episodes from Season Two.